IMPORTANCE OF CLUSTER-MODULE IN THE PROCESS OF EDUCATION AND TRAINING - Abdullayev , Mehriddin Junaydilloyevich; Jamilov , Shohruz Tavakkalovich (Educational Research in Universal Sciences, 2023)
This article describes the importance of the cluster module system in popularizing sports among students in the higher education system and improving the health of young people with health problems.